The Relationship between Caregiver Prompting Behaviors, Parenting Practices, and Adolescent Tobacco Use Outcomes in Black Families. - Velazquez, Efren; Garthe, Rachel C.; Pope, Michell; Avila, Melissa; Romo, Stephanie; Everhart, Robin S.; Jones, Heather A.; Corona, Rosalie (Journal of Child & Family Studies, 2021)
In the current study, we examined how caregiver prompting of tobacco products (e.g., asking a child to empty an ashtray), caregiver monitoring, and caregiver-adolescent communication were associated with adolescents' tobacco use, intentions to use, and efficacy to refuse using tobacco. Caregiver-adolescent dyads were recruited from a southeastern city in the United States. Approximately 48% of the population in this city is Black. Participants included 101 Black caregivers who smoke and their adolescents (M = 14.4 years). Multiple regression analyses (R ranged from 0.10 to 0.44 across models) indicated that higher levels of adolescent-reported caregiver prompting were associated with a higher likelihood of adolescent-reported use and intentions to smoke tobacco products in their lifetime. Caregiver monitoring was associated with lower levels of adolescent tobacco use and intentions to use tobacco, and higher levels of tobacco refusal self-efficacy. General caregiver-adolescent communication was associated with greater tobacco refusal self-efficacy. Differences among caregiver prompting behavior by reporter highlight the importance of obtaining both adolescent and caregiver perceptions. These findings illustrate that caregivers may play a critical role in shaping their adolescents' tobacco-related outcomes through adolescent perceptions of their prompting of tobacco products, as well as their overall knowledge or monitoring of adolescent activities. Highlights: Black caregivers who smoke and their adolescent were both assessed. Prompting behavior from caregivers is associated with adolescent smoking. Caregivers that smoke tobacco products may shape their adolescents smoking behavior.